MENINGKATKAN KEMAMPUAN GURU DALAM MENGEMBANGKAN PENDEKATAN PEMBELAJARAN MELALUI SUPERVISI AKADEMIK DI SD - Eli Marnis (Manajer Pendididikan, 2017)
The purpose of this study was to determine the following matters: (1) increased activity in primary school academic supervision; (2) increasing the ability of teachers to develop teaching approaches centered on students. The research location is SD Negeri 05 Seberang Musi Kepahiang District Bengkulu. Penenilitian a school action research, the research done to find a process of education that best suits the conditions of the school. The study was conducted in two cycles, ie cycle I and II. Data was analyzed using qualitative methods. Subjects were teachers. Based on the results of the actions penbelitian schools that do, it can be concluded as follows: (1) The academic supervision that focuses on the problem of increasing keamampuan teachers in developing learning approach, especially the approach student-centered learning, has increased; (2) There was an increase in the ability of teachers to develop learning approaches, especially on a student-centered approach.